Privacy Preservation in Blockchain IoT - Bhardwaj, Sapna; Sharma, Sagun; Anuradha (International Journal of Computer Sciences and Engineering, 2019)
Blockchain, as a decentralized and appropriated open record innovation in shared system, has received impressive consideration as of late. It uses a connected block structure to confirm and store information, and a linked block structure to verify and store data, and applies the trusted mechanism to synchronize changes in data, which makes it possible to create a tamper-proof digital platform for storing and sharing data. In this paper, the privacy issues caused due to incorporation of blockchain in IoT applications by centering over the utilizations of our everyday use has been discussed. Besides, examining of usage of five security protection methodologies in blockchain-based IoT frameworks namely anonymization, encryption, private contract, mixing, and differential protection has been done. Different architectures for blockchain based IoT applications arediscussed that helps in ensuring privacy while performing a number of operations andtransactions.